Exploring the Earth under the Sea Australian and New Zealand achievements in the first phase of IODP Scientific Ocean Drilling - Exon, Neville (ANU Press, 2017)
"Exploring the Earth under the Sea brings to life the world's largest and longest-lived geological research program, which has been drilling over many decades at many locations deep below the ocean floor to recover continuous cores of sediment and rock. Study of these materials has helped us understand how the Earth works now, how it has worked in the past and how it may work in the future. The cores are a wonderful source of information on the dynamic processes that form and reform the Earth, both beneath the ocean and on land. The results have revealed climate and oceanographic change on different time frames, the history of life in the sea and on land including global mass extinctions, the extraordinary story of the great masses of 'extremophile' microbes that live beneath the sea bed, the nature of the giant earthquakes and tsunami generated at the trenches where tectonic plates collide, and the nature of submarine volcanoes and metalliferous deposits. This book outlines the technology and enduring international partnerships that underlie the scientific ocean drilling accomplished by the first phase of IODP, currently involving 23 countries. It highlights the important role of Australian and New Zealand scientists in the program, and the great scientific benefits we have derived from our partnership since joining IODP in 2008. As well as the scientific summaries, there are personal accounts by shipboard scientists of how they found life at sea on two-month expeditions, working 12-hour shifts on a noisy drill ship."